SISTEM PENJAMINAN MUTU INTERNALSEKOLAH UNTUK MENINGKATKAN MUTU LULUSAN - Darmaji Darmaji; Achmad Supriyanto; Agus Timan (Universitas Negeri Malang, 2019)
Abstract: This article aims to describing the system of guaranteeing internal quality of schools to ensure that the quality of graduates is able to be competitive with other school outcomes. This study explains that guaranteed internal quality of schools should at least refer to the standards set by the government, namely the National Education Standards (SNP). The school strives to implement guaranteed internal quality, because the quality of output is influenced by the process of guaranteeing the internal quality of the school, the focus of the school in ensuring the quality and implementation of guaranteed quality to ensure school quality. Using interview techniques with the principal who aims to determine the policies implemented in ensuring quality, and make observations about the implementation of guaranteed quality and also conduct documentation studies in schools (qualitative descriptive). The impact that results from ensuring the quality of schools is that schools are capable of achieving academic and non-academic achievements and are able to compete with other school graduates.Abstrak: Artikel ini bertujuan untuk mendeskripsikan sistem penjaminan mutu internal sekolah gunamemberikan kepastian bahwa mutu lulusan yang mampu berkompetisi dengan mutu luaran sekolah yang lain. Sekolah berupaya sekuat tenaga untuk melaksanakan penjaminan mutu internal karena mutu output sangat dipengaruhi oleh proses penjaminan mutu internal sekolah, fokus sekolah dalam melaksanakan penjaminan mutu danbentuk pelaksanaan penjaminan mutu yang dilaksakanan untuk memastikan mutu sekolah. Dengan menggunakan teknik wawancara kepada kepala sekolah bertujuan untuk mengetahui kebijakan yang dilaksanakan dalam penjaminan mutu, melakukan pengamatan tentang pelaksanaan penjaminan mutu, serta melakukan studi dokumentasi di sekolah (deskriptif kualitatif). Dampak yang dihasilkan dari pelaksanaan penjaminan mutu sekolah yakni sekolah mampu berprestasi baik dibidang akademik dan non akademik dan mampu bersaing dengan para lulusan sekolah yang lain.